PENGARUH KEPERCAYAAN, KENIKMATAN DAN NORMA SUBJEKTIF TERHADAP NIAT BERMAIN GAME ONLINE YANG DIMEDIASI OLEH KEPUASAN - Julianto Wijaya Akoi Lim; Yuliana, Jovito Bryant Budiman, Suwandi, Ivan Felix (ADISAM PUBLISHER, 2024)
Technology is developing rapidly and becoming part of society, especially among children to adolescents. The development of this technology has resulted in a new form of entertainment in the form of games. Online games are one of the results that arise as a result of technological developments. The research was conducted using a quantitative approach and distributing questionnaires online. The sampling method used in this research is Cluster Disproportionate Random Sampling. The method that will be used as a medium for data analysis in this study is SEM. This analysis will be carried out by utilizing the AMOS application. The test results show that Online Gaming Enjoyment has a significant and positive effect on Satisfaction of Playing Online Games and Subjective Norms Instrumental Use and Trust in Online Game Ritualized Use has a significant and positive effect on Satisfaction of Playing Online Games. Appropriate improvisation of the Game can increase the enjoyment of playing the Game so that it can reach more players. This is the reason to improve the features in the Game such as Graphics, Songs, Community, Story, World Building and other aspects